Convergence Analysis of Two Parallel Methods for Common Variational Inclusion Problems Involving Demicontractive Mappings - Thanasak Mouktonglang; Kanyuta Poochinapan; Pariwate Varnakovida; Raweerote Suparatulatorn; Sompop Moonchai (Journal of Mathematics)
The main objective of this article is to propose two novel parallel methods for solving common variational inclusion and common fixed point problems in a real Hilbert space. Strong convergence theorems of both methods are established by allowing for some mild conditions. Moreover, numerical studies of the signal recovery problem consisting of various blurred filters demonstrate the computational behavior of the proposed methods and other existing methods.